Analisis Strategi Peningkatan Literasi Dasar pada Siswa Sekolah Dasar di Surabaya untuk Mendukung Peningkatan Nilai Pisa (Program for International Student Assessment): Systematic Literature Review - Hariyati, Mutty; Arianto, Fajar; Martadi, Martadi; Agusti, Fiqrie Restia (Library and Information Science Study Program, Faculty of Humanities, Univ. Diponegoro, 2024)
Background: The national level of basic literacy skills in Indonesia, as assessed by the Program for International Student Assessment (PISA), remains alarmingly low. This is an anomaly considering the implementation of the School Literacy Movement (Gerakan Literasi Sekolah/GLS) at the elementary school level, which has introduced various strategies for enhancing basic literacy skills.Objective: Therefore, this study aims to analyze strategies for improving basic literacy skills among elementary school students to support an increase in PISA scores.Methods: The research method employed in this study is the Systematic Literature Review (SLR), which involved analyzing journal articles published between 2019 and 2024 related to strategies for enhancing basic literacy skills in elementary school students in Surabaya. The researchers reviewed five journal articles obtained from Google Scholar.Results: The findings reveal several strategies that have been implemented to improve basic literacy skills among elementary school students, including literacy habituation through GLS and teaching methods such as the formation of literacy clubs, reading aloud, and the use of visual media. Necessary support includes the provision of facilities and infrastructure, awarding incentives, and collaborative support from all stakeholders. Meanwhile, obstacles include the absence of a dedicated literacy team, inadequate facilities and infrastructure, and changes in school leadership policies regarding literacy activities.Conclusion: The strategy to improve basic literacy involves holistic efforts through habitual literacy activities, student-centered teaching methods, and collaborative support from all stakeholders (schools, parents, communities, governments, and private sectors), aiming to enhance students' critical thinking, global mindset, and PISA performance while addressing challenges like inadequate resources and policy changes.